Uma metodologia para a estimativa de parâmetros no cálculo da propagação de enchentes - Mascarenhas, Flavio Cesar Borba (1980)
The unsteady varied characteristic of the flood wave movement contributes for the appearing of new values of parameters, which are frequently much different of that established by classical hydraulics. The objective of this work was to obtain a set of parameter values for a given reach of a river and for different flood magnitudes, with the use of a numerical procedure by finite difference in order to integrate the partial derivative equations that describe the phenomenon of the flood wave movement. The main parameters to be adjusted were the Manning's roughness coefficient and the hydraulic radius exponent, both of them included on the friction slope expression. A third important parameter was the lateral inflow contribution at the reach of the river in study. For the application of the model it was selected a reach between the fluviometric gauges of Marcelino Ramos and Itá, at Uruguai river. Six floods were calibrated and it was established a trend for the variation of the roughness coefficient with the depth of the flow.